IJTIHAD POLITIK NU: NEGARA PANCASILA ADALAH NEGARA ISLAM - Fajar Syarif (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2019)
The debate over the relationship between religion and the state reappeared when the New Order regime was at its peak of power, the 1980s. This has a fundamental need to strengthen the Unitary State of the Republic of Indonesia (NKRI) and establish Pancasila as the only state ideology and the only principle for religious and social organizations. This need certainly created an extraordinary paradigmatic controversy among all components of the nation, especially Muslims: between following the political will of the New Order or remaining a supporter of the establishment of an